Komikisasi Hadis: Arah Baru Syarah Hadis Di Indonesia Studi Kritis atas 99 Pesan Nabi: Komik Hadis Bukhari-Muslim - By Miski (Millati: Journal of Islamic Studies and Humanities, 2017)
Creating comic of hadith is a new trend of Hadith studies in Indonesia. One of the important works is Kritis atas 99 Pesan Nabi: Komik Hadis Bukhari-Muslim (a critical of 99 Prophet Messages: Bukhari-Moslems Hadith Comic) by vbi_djenggotten or Veby Surya Wibawa. As a work, it seems interesting to be critically analyzed to reinforce the position of the work among other syarah of hadiths, at least including the description of the work, the typology of understanding and the content. To get a comprehensive description, this article uses a normative approach, content analysis and purely library research (library research). As a result, it is found that descriptively, this comic even from the very beginning is only to explore hadiths with the choices contained in Ṣaḥīḥ al-Bukhārī by al-Bukhārī and Ṣaḥīḥ Muslim by Muslim ibn al-Ḥajjāj, but there are some hadiths which come from outside these legitimate works coming from Musnad Aḥmad by Aḥmad ibn Ḥanbal and Sunan Abī Dāwūd by Abū Dāwūd. In addition, by taking samples of two hadiths entitled “Istri Ideal “ (Ideal Wife), typologically, it appears to be in the category of textual hadith syarah. Moreover, in content, the illustration about women contained cannot be denied that can create a variety of criticism, especially when it is viewed from a feminist perspective, because it impresses gender biased.